2023
DOI: 10.3390/molecules28176407
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Pre-Treatment and Drying Methods on the Quality of Dried Carrot Properties as Snacks

Anna Ignaczak,
Agnieszka Salamon,
Jolanta Kowalska
et al.

Abstract: The aim of the current research was to evaluate the effect of pre-treatment and drying methods on the properties of dried carrots. Carrots were blanched (B) (1 or 3 min) or osmotic dehydrated (OD) (15 or 30 min) and dried by either convection (CD), microwave-convection (MW-CD), microwave-vacuum (MVD), or freeze-drying (FD). FD carrots showed the highest dry matter content (93.6–95.8%) and the lowest water activity (0.24–0.38). MVD carrots had lower dry matter content (79.5–95.8%) and two times more water activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
0
0
Order By: Relevance
“…The quality of dried products depends to a large extent on the preliminary preparation of the raw material for drying. In this aspect brief heat treatment to inactivate enzymes, eliminate appearance of foreign flavours and reduce possible initial contamination improve the quality of the ready products [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The quality of dried products depends to a large extent on the preliminary preparation of the raw material for drying. In this aspect brief heat treatment to inactivate enzymes, eliminate appearance of foreign flavours and reduce possible initial contamination improve the quality of the ready products [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The study found that drying rate increased with increasing infrared power and that shrinkage rate, rehydration rate, and color parameters were influenced by process variables. The study by Ignaczak et al [4] showed that freeze-dried carrot samples had a high dry matter content and low water activity; microwave vacuum-dried samples had large color differences, while those dried by convection and freeze-drying had smaller color differences. Radiant Energy Vacuum (REV) dehydration was an advanced method of fast, low-temperature drying, but the equipment manufacturing and installation costs were high [2].…”
Section: Introductionmentioning
confidence: 99%